ʿAql u ʿishq yā Munāẓarāt-i khams - Iṣfahānī, Ibn Turka (Miras Maktoob, ISBN: 9789004365452., 2019)
Ibn Turka Iṣfahānī (d. 835/1432) stemmed from a well-educated family in Isfahan. In 789/1387, following Tīmūr Lang's (d. 807/1405) massacre of the population of Isfahan, he and his older brother were among the artists and scholars whose lives were spared and marched off to the capital Samarqand. Ibn Turka studied the Islamic sciences under this brother for 25 years. He then went on a study tour that took him to the classrooms of such great scholars as Shams al-Dīn Fanārī (d. 834/1451) and Sirāj al-Dīn al-Bulqīnī (d. 805/1403), to finally return to Isfahan. With more than 50 philosophical works to his name, Ibn Turka is seen as a key figure in the amalgamation of voam, Peripatetic and Illuminationist philosophy and mysticism, leading eventually to the Transcendent Philosophy of Mullā Ṣadrā (d. 1045/1635). Written in a beautiful Persian, the present work describes the struggle between divinely-inspired love and reason, ending in their glorious unification.